AKUNTANSI DAN LAPORAN KEUANGAN UNTUK BIAYA LINGKUNGAN DAN KEWAJIBAN LINGKUNGAN - Sri Adela Fitri (JURIS (Jurnal Ilmiah Syariah), 2018)
Environmental Accounting aims at increasing numbers of relevant information issued for those who need and use the information. Other purposes of the importance of releasing Environmental Accounting is something to do with environmental conservation activities conducted by either private enterprises or governmental institutions that cover public organization needs and local public enterprises.  Furthermore, has become relevant to enterprises (either company, non-profit organization, or government) because of limited availability of natural resources and environmental contamination has become a great issue all over the world. Several efforts have been made in national and international levels to protect environment and to get rid off the effects of pollution. Therefore, there is a tendency among enterprises to inform societies about the data on their environmental policy, environmental management programs and the impacts toward financial performance